A RETROSPECTIVE COHORT STUDY IN AN INDIAN TERTIARY CARE HOSPITAL ON BREAST LESION CLASSIFICATION BY THE IAC YOKOHAMA SYSTEM USING FNAC - Singh, Abhishek; Singh, Seema; Tiwari, Sanchit; Shukla, Shivendra Dutt (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The International Academy of Cytology (IAC) Yokohama system was used to categorize breast lesions as the major goal of this investigation. Methods: Between January 2022 and March 2023, this study on breast fine needle aspiration cytology (FNAC) was carried out at a tertiary care facility in north India. This System of reporting breast cytopathology was used to classify a total of 100 patients. Histopathology correlation was available in 40 cases; Malignancy risk, sensitivity, specificity, and diagnostic precision were assessed. Results: Breast FNAC cytology was divided into five groups using the new IAC Yokohama system and discovered C1: Insufficient material (6%), C2: Benign type (72%), C3: Atypical type (05%), C4: Suspicious type of malignancy (06%), C5: Malignancy (11%). When histopathological reports were available, FNACs were connected with them. The likelihood of cancer, the precision, sensitivity, and specificity of the diagnosis were all calculated. Conclusion: The IAC Yokohama System for reporting breast cytopathology governs how breast FNAC are categorized, which offers an excellent method for reporting breast cytopathology with a uniform method of reporting and clear definition of each category as well as clear communication between pathologists and clinicians regarding the risk of malignancy and subsequent management.